إيجابيات المشركين وسلبياتهم من خلال القرآن الكريم ( دراسة نموذجية): The merits and demerits of the polytheists as illuminated by the Holy Quran” (An exemplary study) - Afshin Shafiq,; Kalsoom Asghar,; Husna Qayumi, (Al Manhal Research Journal, 2023)
Indeed, Muhammad, peace be upon him, is a prophet sent to the Arabs to get them from darkness and ignorance to the light of Islam. It is evident that the Arabs, before Islam, were not in the state they are in today, living a happy and good life. Ignorance and misguidance were prevalent among them. Examples of their misguidance include associating partners with Allah, denied the Hereafter, and committed heinous acts such as killing daughters, engaging in interest, and many others. However, when we look at their conditions during that period, we find some unique qualities among them that were considered positive, such as hospitality, generosity, good neighborliness, bravery, and others related to beliefs and worship, like the belief in the existence of Allah, performing the circumambulation of the Kaaba, the Sa'i (running) between Safa and Marwah, sacrificial offerings, the reverence of sacred months, and the veneration of the Kaaba, among others. Insha'Allah, we will elaborate on the positives and negatives of the polytheists in this paper, in detail.